The effective learning process in 5E flipped learning environment: A case study of medical assistant students - Bala Krishnian Muniandy; Por Fei Ping; Rames Prasath Mahatan Rai (University of Muhammadiyah Malang, 2023)
Different studies have addressed different aspects of flipped learning but its practices and issues with integrated 5E learning cycles in higher education in Malaysia context still need to be explored. This case study is an attempt to explore medical assistant undergraduate students’ learning experiences in the 5E flipped learning environment (5EFL). Varied forms of data were collected, including (1) semi-structured individual interviews with students, (2) student focus discussions, (3) participant learning journals, and (4) classroom observations. Thematic analyses were conducted to analyze qualitative data respectively. Multiple methods were employed to establish the trustworthiness of the study. The findings indicated that students valued real-time interactions with peers and the instructor. In addition, five themes emerged from the study a) Supportive Learning Process, b) Organized and Well-Structured Method, c) Enhance Teacher’s Supportive Role, d) Facilitate Students' Role, and e) Enhance Perceived Competence Level in Learning. This study found learners improved their quality of work in 5EFL. Thus, this 5EFL environment played an important role in enriching learners’ cognitive load in the learning process.